A study of the use of augmented reality in learning: impacts on increasing students' critical thinking skills / Hernawan Sulistyanto ... [et al.] - Sulistyanto, Hernawan; Prayitno, Harun Joko; Narimo, Sabar; Anif, Sofyan; Sumardjoko, Bambang; Wardhani, Novia Wahyu (Universiti Teknologi MARA, 2024)
The ability to think critically could be improved by using proper learning media. At present it is found that many students have very low critical thinking skills as a result of the ease of learning facilities provided by advances in information technology and computers for society 5.0. This paper aimed to investigate the impact of using Augmented Reality (AR) in learning on improving the critical thinking skills of vocational school-level students in Indonesia. The research method used Design Based Research (DBR) with the main stages of identifying and analyzing problems, designing solutions, repeating cycles in testing and improving product designs, as well as reflection to produce design principles and implementation. A total of 98 students from vocational schools using cluster random sampling techniques were used as samples for this research. Testing the effectiveness by conducting a sample paired test. The results obtained from the application of AR were an increase in students' abilities in aspects of analysis of 96.82%, inference of 79.77%, interpretation of 93.16%, explanation of 95,31%, evaluation of 69.09%, and self-regulation of 93.17%. Based on the results obtained, it can be concluded that the use of AR in learning can massively improve students' critical thinking skills. With these findings, AR can be recommended as one of the best technology choices that can be used widely in delivering learning materials to improve students' thinking skills in this century.